1987
DOI: 10.1029/jb092ib03p02641
|View full text |Cite
|
Sign up to set email alerts
|

Age of tilted reefs, Hawaii

Abstract: Submerged carbonate reefs are preserved as a series of submarine terraces between Molokai and Hawaii along a 200‐km span of the southeastern Hawaiian Ridge. Limestones from two of the terraces have been sampled from submersibles and dated radiometrically at 13 and 120 ka. Recognition that the terraces are tilted permits assignment of about a dozen terraces from 150 to 1300 m depth to eight general reef platforms. These reefs were drowned by the combined effects of island subsidence and sea level rise at the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 7 publications
3
63
0
Order By: Relevance
“…Ground-water use averaged about 394 Mgal/d from all sources in 1980 (Nakahara, 1980). Of this, about 81 percent, or 318 Mgal/d, was pumped from the volcanicrock aquifers of the island, with 238 Mgal/d being pumped from the southern Oahu area alone.…”
Section: Ground-water Discharge and The Development Of Ground Water Imentioning
confidence: 99%
See 1 more Smart Citation
“…Ground-water use averaged about 394 Mgal/d from all sources in 1980 (Nakahara, 1980). Of this, about 81 percent, or 318 Mgal/d, was pumped from the volcanicrock aquifers of the island, with 238 Mgal/d being pumped from the southern Oahu area alone.…”
Section: Ground-water Discharge and The Development Of Ground Water Imentioning
confidence: 99%
“…Moore and Campbell (1987), in a study of tilted, deeply submerged reefs in the Hawaiian islands, concluded that subsidence ended about 0.5 Ma after the end of shield-building volcanism. Moore (1987) provides a comprehensive summary of this evidence for the Hawaiian islands, together with new evidence and analysis, and concluded that most of the volcanoes have subsided 6,500 to 13,000 ft. Lavas that originally were erupted subaerially and have textural characteristics of subaerial lavas have since been carried to great depths by this subsidence.…”
Section: Geologic Settingmentioning
confidence: 99%
“…The Hilo tide gage, located 30 km north-northwest of the drill hole area, has recorded an average absolute subsidence rate of 2.4 mm/yr for the past 38 years (Moore, 1987). A similar rate (2.5 mm/yr) was determined for the past half million years on the basis of the age of drowned reefs off Kohala volcano on the northern part of the island (Moore and Campbell, 1987). We assume that the subsidence rate at the drill hole area is similar to that at Hilo because a compilation of seismic evidence indicates that depression of the base of the crust is similar at Hilo and the drill hole area (Moore, 1987, his fig.…”
Section: Rate Of Growth Of Kilauea Volcanomentioning
confidence: 70%
“…The 1 ,300-m-deep terrace is about 800 m deeper than a 500-m-deep terrace that formed about 850,000 years ago (Moore and Campbell, 1987). If the Molokai subsidence rate was comparable to that of northern Hawaii (2.5 millimeters per year (mm/yr)) during the period between formation of the 1 ,300-m-deep terrace and the 500-m-deep terrace, then the estimated age of the 1 ,300-m-deep terrace is about 1.17 million years.…”
Section: Wailau Debris Avalanchementioning
confidence: 90%